Aeromonas spp. y Plesiomonas shigelloides en bivalvos, cieno y aguas del Golfo de Nicoya, Costa Rica - Rodríguez, Evelyn (1989)
Bivalves, mud, and surface water were collected at three different sites of the Gulf of Nicoya, Costa Rica, in search of Aeromonas spp. and Plesiomonas shigelloides. For their isolation, these bacteria were enriched in alkaline peptone water and streaked on MacConkey agar and on brilliant green bile inositol agar. This was followed by the biochemical tests necessary for their identification. Thirty-five strains of A. hydrophila, 58 of A. caviae, 43 of A. sobria, and 7 of P. shigelloides were isolated. None of these predominated nor was there any indication of a seasonal distribution along the 15 month's duration of the study. Seven strains of A. hydrophila and two of A. sobria showed the biochemical characteristics associated with toxin production (positive Voges-Proskauer and lysine decarboxylase tests). These species are widely distributed in the gulf and there is risk of contracting an infection while bathing or when eating raw bivalves from this area